Analisis Pengaruh Komunikasi Pemasaran, Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Pelanggan Produk Uniqlo - Ruchiat Nugraha, Aat; Wahyono, Dwi; Siregar, Achiruddin; Setianti, Yanti; Tampubolon, Septrina (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research was conducted to analyze the influence of marketing communications, service quality and trust on customer loyalty for Uniqlo products. This type of research is quantitative research. The population in this research is consumers who have come at least twice to Uniqlo. The sample used in this research was 93 respondents. Based on the results of this research, marketing communications has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty, and trust has a positive and significant effect on customer loyalty. The resulting Adjusted R Square value is 56.4%. Simultaneously, the research results show that marketing communications, service quality and trust have a positive and significant effect on customer loyalty.